Determining the factors to engage in batik business: A study among batik entrepreneurs in East Cost Malaysia - Nurul Ashykin Abd Aziz; Nurul Aien Abd. Aziz; Noreen Noor Abd Aziz; Siti Fariha Muhamad; Afifah Hanim Md Pazil (Research Academy of Social Sciences, 2016)
This study is to examine about determining the factors to engage in batik business among entrepreneurs in East Cost Malaysia. The purpose is to define the factors that influence the batik entrepreneurs conducting their business. This study was involved 160 entrepreneurs from 3 east cost state in Malaysia which is Kelantan, Terengganu and Pahang who run the batik business. Simple Random Sampling has applied in this study to the specific target population. This paper also discusses the findings of the study and to examine whether the objectives of this study can be achieve. The study comes out with findings and analysis of data from the conducted study. By according to the study, the dimension factors that been tested in this study was location, demand, resources and culture. From the findings, it can be concluding that the culture determines the entrepreneurs to engage in batik business. It also concludes that the resources give an impact to entrepreneur to engage in batik business although it influenced to a certain percentage. The study further concludes that the demand determines the engagement of entrepreneur in batik business. Finally, the study concludes that the location influence entrepreneur to engage in batik business through the strategic location where most of their business is located at the main city of state.